2014
DOI: 10.1164/rccm.201407-1287oc
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Fibrocytes as Biomarker of Prognosis in Hermansky-Pudlak Syndrome

Abstract: Rationale: The rate of progression of most interstitial lung diseases (ILD) is unpredictable. Fibrocytes are circulating bone marrow-derived cells that have been implicated in the pathogenesis of lung fibrosis. Hermansky-Pudlak syndrome (HPS), a genetic cause of ILD in early adulthood, allows for study of biomarkers of ILD in a homogeneous population at near-certain risk of developing fibrotic lung disease.Objectives: To test the hypothesis that, in subjects with HPS, the number or phenotype of circulating fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 38 publications
3
39
0
Order By: Relevance
“…In addition, patients with HPS-PF have been found to have increased numbers of circulating CXCR4-positive fibrocytes compared with subjects with HPS without lung disease or healthy control subjects (39). Increasingly, as suggested for IPF, studies point to the type II alveolar epithelial cell as central in the pathogenesis of HPS pulmonary fibrosis.…”
Section: Pulmonary Fibrosis: Pathogenesismentioning
confidence: 98%
“…In addition, patients with HPS-PF have been found to have increased numbers of circulating CXCR4-positive fibrocytes compared with subjects with HPS without lung disease or healthy control subjects (39). Increasingly, as suggested for IPF, studies point to the type II alveolar epithelial cell as central in the pathogenesis of HPS pulmonary fibrosis.…”
Section: Pulmonary Fibrosis: Pathogenesismentioning
confidence: 98%
“…15 They have been implicated in the pathogenesis of several interstitial lung diseases. [32][33][34] Previous data, largely on animal models, have suggested that fibrocytes are also involved in the pathogenesis of lung fibrosis in SCD. 17 Our previous data on patients show that circulating fibrocytes are increased and activated in patients with SCD compared with control participants; circulating fibrocytes also are increased further during VO crises.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multiple studies have examined these cells, defined as expressing both the common leukocyte antigen CD45 and collagen I, when isolated from the peripheral blood 65 as biomarkers for disease severity in IPF and in other non-IPF diseases. [67][68][69][70] The fibrocyte bridges our categories of matrix and remodeling and immune dysregulation as it exhibits properties of both. "Bursts" of fibrocytes did not correlate with death in a study of Hermansky-Pudlak syndrome, 67 suggesting that deterioration or death does not correlate with absolute fibrocyte numbers and potentially limits enthusiasm for the fibrocyte as a biomarker.…”
Section: Circulating Fibrocytesmentioning
confidence: 99%
“…[67][68][69][70] The fibrocyte bridges our categories of matrix and remodeling and immune dysregulation as it exhibits properties of both. "Bursts" of fibrocytes did not correlate with death in a study of Hermansky-Pudlak syndrome, 67 suggesting that deterioration or death does not correlate with absolute fibrocyte numbers and potentially limits enthusiasm for the fibrocyte as a biomarker. 71 Further study will be necessary to assess absolute numbers of fibrocytes, their behavior over time, and their relationship with pulmonary function.…”
Section: Circulating Fibrocytesmentioning
confidence: 99%